Sevoflurane at 1.0 MAC together with remifentanil and propofol produces clinically acceptable intubation conditions at the vocal cords: A prospective randomized study. (June 2017) - Ovari, Attila; Bicker, Ilona; Machmueller, Susann; Schuldt, Tobias; Sauer, Martin; Soltesz, Stefan; Noeldge-Schomburg, Gabriele; Mlynski, Robert; Mencke, Thomas
Objective: The overall intubation conditions after tracheal intubation with remifentanil, propofol, and sevoflurane at 1.0 minimum alveolar concentration (MAC) are worse than with rocuronium at 0.45 mg/kg. Therefore, we compared the intubation conditions and laryngeal morbidity (vocal cord injuries, hoarseness, and sore throat) with sevoflurane at 1.2 and 1.4 MAC versus 1.0 MAC. Methods: In this prospective clinical trial, 90 patients were randomized to 3 groups: the sevoflurane 1.0, 1.2, and 1.4 MAC groups. At 3 min, tracheal intubation was performed and the patients' intubation conditions were assessed. The vocal cords were examined for injury by videolaryngoscopy. Additionally, the incidence and severity of laryngeal morbidity were compared between women and men. Results: Acceptable intubation conditions were seen in 72% of the patients without significant differences between the groups. Overall, vocal cord injuries (oedema) occurred in three (4%) patients. Women reported sore throat more often than men (51% vs. 21%, respectively). Conclusions: Intubation conditions were not improved with higher sevoflurane concentrations. The incidence and severity of sore throat were greater in women than men. Trial registration: ClinicalTrials.Gov: NCT 01896245